マクロライドのマクロファージ活性化による肺炎球菌の鼻咽頭定着抑制効果 - 岩永, 直樹 (Oxford University Press, 2015)
Nagasaki University (長崎大学) 博士(医学) Streptococcus pneumoniae (pneumococcus) colonizes mucosal surfaces of the upper respiratory tract (URT), resulting in invasive disease. Macrolides are known for their immunomodulatory effects. We investigated the potency of macrolides to reduce pneumococcal colonization by activating host innate immunity. Methods. The kinetics of colonization, cellular response, and inflammatory cytokine levels in the URT were assessed after nasal inoculation of pneumococci. EM900 (a novel 12-membered nonantibiotic macrolide with an immunomodulatory effect) was orally administered throughout the experiment. Survival was evaluated for 10 days. Macrolide-mediated CCL2 production from peritoneal macrophages was determined by enzyme-linked immuosorbent assay. The cell-signaling pathway was analyzed by means of Western blotting and gene silencing assays. Results. Streptococcus pneumoniae was significantly reduced from EM900-treated mice 14 days after pneumococcal inoculation.Macrophage recruitment and Ccl2messenger RNA expression were promoted. CCL2 production fromperitonealmacrophages was significantly induced bymacrolides and was dependent on NF-κB phosphorylation through the myeloid differentiation primary-response gene 88-or TIR domain-containing adapter-inducing interferon-β-mediated pathway. Mortality of mice with invasive pneumococcal disease was improved by pretreatment with EM900. Conclusions. Macrolidesmay inhibit invasive pneumococcal infections by accelerating the clearance of pneumococcal nasopharyngeal colonization via promotion of macrophage-mediated innate immunity. 長崎大学学位論文 学位記番号:博(医歯薬)甲第790号 学位授与年月日:平成27年8月5日 Author: Naoki Iwanaga, Shigeki Nakamura, Kazuhiro Oshima, Toshiki Kajihara, Takahiro Takazono, Taiga Miyazaki, Koichi Izumikawa, Katsunori Yanagihara, Akihiro Sugawara, Toshiaki Sunazuka, Satoshi Omura, Shigeru Kohno Citation: Journal of Infectious Diseases, 212(7), pp.1150-1159; 2015 Nagasaki University (長崎大学), 博士(医学) (2015-08-05) doctoral thesis